IMPROVING STUDENTS ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT THROUGH MIND MAPPING TECHNIQUE - Eliye Yuli Yenti and Meisuri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study aims to improve students’ achievement in writing descriptive text through Mind Mapping technique. This study was conducted by using classroom action research. The subject of the research was class VIII-1 SMP Negeri 3 Tanjung Beringin which consisted of 30 students. The research was conducted in two cycles and every cycle consisted of three meetings. The instruments of collecting data were quantitative data (writing tests) and qualitative data (diary notes, observation sheet, and interview sheet). In analyzing the data, the students’ mean was 60.46 for the test I, in the test II was 67.5, and 74.06 in test III. Based on the diary notes, observation sheet, and interview sheet, it was found that teaching-learning process ran well, students were active, enthusiastic, and interested in writing. The research showed that the Mind Mapping Technique significantly improved students’ writing achievement in descriptive text.